2000
DOI: 10.2516/ogst:2000026
|View full text |Cite
|
Sign up to set email alerts
|

A Scale-Up Strategy for a Commercial Scale Bubble Column Slurry Reactor for Fischer-Tropsch Synthesis

Abstract: Résumé -Stratégie d'extrapolation vers un réacteur industriel de synthèse Fischer-Tropsch en colonne à bulles avec catalyseur en suspension -Les réacteurs à colonne à bulles trouvent de plus en plus d'applications dans l'industrie. Cette technologie est très en vue dans les procédés de transformation du gaz naturel en carburants liquides et en oléfines légères par le procédé de Fischer-Tropsch. On rencontre des problèmes considérables pour l'étude et l'extrapolation de ce type de réacteur. D'abord, il faut une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 51 publications
(123 reference statements)
3
55
0
1
Order By: Relevance
“…Krishna [2] gave a summary of flow processes studied in bubble-column reactors. Air bubble swarms were made to rise vertically through the water fill at different pressure stages.…”
Section: Overview Of the Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Krishna [2] gave a summary of flow processes studied in bubble-column reactors. Air bubble swarms were made to rise vertically through the water fill at different pressure stages.…”
Section: Overview Of the Relevant Literaturementioning
confidence: 99%
“…Recent developments have shown that multiple-jet Pelton turbines working under backpressure conditions in hydro-electric power plants may be an adequate choice in the case of (1) major tailwater-level oscillations, (2) full turbine operation between 0 and 100% being required without any major efficiency loss, and (3) the need to reduce the difference in turbine and pump levels to minimise construction cost. Figure 1 is a section through the typical arrangement of a vertical-shaft backpressure Pelton turbine.…”
Section: Introductionmentioning
confidence: 99%
“…In the homogeneous flow regime there is a narrow bubble size distribution and the researchers use frequently the Sauter−mean bubble diameter d s for their mass transfer calculations. The bubbles rise uniformly in nearly straight lines and have roughly uniform bubble size (Krishna, 2000;Lucas et al, 2005). Therefore, it is a reasonable simplification in the homogeneous flow regime to use the mean bubble diameter and disregard the bubble size distribution.…”
Section: New Approach For Prediction Of Volumetric Liquid-phase Mass mentioning
confidence: 99%
“…The dimensionless gas density ratio is probably needed because the correlation of Wilkinson et al (1994) was derived for pressures up to 1.5 MPa only, whereas the present data extend up to the pressure of 4 MPa. It is worth noting that Krishna (2000) also used such a dimensionless gas density ratio for correcting his correlations for large bubble rise velocity and dense−phase gas holdup. Figure 1 illustrates the decrease of the product f c (ρ G /1.2) -0.07 with increasing Eo.…”
Section: Ta Re Momentioning
confidence: 99%
“…In section 4.1, it was explained that gas channeling in the lower column region resulted in a negligible decrease in gas holdup when additional fiber is added to the column because the fiber dispersion is not uniform. Krishna (2000) argued that the slurry dispersion coefficient is proportional to the liquid circulation velocity and bubble column diameter. At the fiber mass fraction where channeling is observed, more fibers disperse in the larger diameter bubble column leading to a more uniform fiber dispersion.…”
Section: Fiber Suspensionsmentioning
confidence: 99%